Peningkatan Proses Pengolahan Limbah Sewage Treatment Plant dalam Pencapaian Baku Mutu Air Limbah Dengan Metode Six Sigma di PT. XY - Ririn Mulyani; Alfiya Rokhmah; Fajar Anzari (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
. PT. XY is a company engaged in the printing sector, especially in the security products sector, which is required to process its wastewater so that it can meet the required wastewater quality standards, especially in the processing of domestic waste originating from human waste and other consumption waste such as washing water, rinsing and so on. A Sewage Treatment Plant is a domestic liquid waste processing installation to process residual domestic liquid waste so that it becomes clear and is no longer harmful to the environment. The problem that arises is one of the measurement parameters in the wastewater quality standard, namely total coliform (coliform bacteria), which has not met the requirements for several months. This study aims to process domestic waste in the sewage treatment plant process with the six-sigma method to achieve results according to the requirements of the liquid waste quality standard. It is safe to be discharged into water bodies. The results of this study from 6 parameters 5 parameters meet the wastewater quality standards, namely: pH, Total Suspended Solids / TSS, Biochemical Oxygen Demand5 / BOD5, Chemical Oxygen Demand / COD, Oil and fat, while the average level of Total Coliform in a year is 6,448 MPN / 100 ml, not yet meeting the wastewater quality standards of 3,000 MPN / 100 ml. The results of the six-sigma calculation found a result of 1.5 Sigma (σ) where the process is in the non-competitive category